Diffusion of skyrmions: the role of topology and anisotropy - M Weißenhofer; U Nowak (New Journal of Physics, 2020)
We study the diffusive motion of metastable localized spin structures with various topological charges by combining atomistic spin model simulations with an extension to the Thiele equation taking into account translational and rotational degrees of freedom. The Brownian motion of skyrmions is shown to obey markedly different diffusion laws depending on their topological properties. We demonstrate that skyrmions with topological charges Q = −1 and Q = 0 exhibit anisotropic translational diffusion due to their non-circular shape. The coupling between rotational and translational Brownian motion, however, causes memory of the initial orientation to be lost on a timescale governed by the effective rotational diffusion coefficient, ultimately leading to isotropic diffusion in the long time limit.